Spectres marxistes du féodalisme : le passé d’une interprétation ? - 1ère partie - Blaise Dufal (L'Atelier du CRH)
The place of Marxism in French historiography of the 20th century, and particularly in medievalism, is tenuous and repressed. This study describes the different forms of penetration, dialogue, uses as well as refusal and opposition to Marxism by French medievalists. This panorama allows us to grasp the singularity of a particular Marxist moment which revolves around the notion of feudalism from 1963, particularly around the Center for Marxist Study and Research. The historical work around this Marxist notion was continued by the Society for Study of Feudalism from 1976, in particular by Guy Bois, Alain Guerreau, Jean-Claude Schmitt and Daniel Tollet and deployed multiple intellectual aspects, opening up to important scientific turning points. This marginal Marxist adventure in French medievalism ended quite abruptly, to sink into oblivion in the second half of the 1980s.